Anatomical variation of mesophyll conductance due to salt stress in Populus cathayana females and males growing under different inorganic nitrogen sources. (8th February 2021) - Liu, Miao; Liu, Xiucheng; Du, Xuhua; Korpelainen, Helena; Niinemets, Ülo; Li, Chunyang
Abstract: Synergistic regulation in leaf architecture and photosynthesis is essential for salt tolerance. However, how plant sex and inorganic nitrogen sources alter salt stress-dependent photosynthesis remains unknown. Leaf anatomical characteristics and photosynthesis of Populus cathayana Rehder females and males were investigated under salt stress conditions combined with nitrate NO3 − and ammonium NH4 + supplies to clarify the underlying mechanisms. In salt-stressed females, we observed an increased mesophyll spongy cell density, a reduced chloroplast density, a decreased surface area of chloroplasts adjacent to the intercellular air space ( S c / S ) and an increased mesophyll cell area per transverse section width ( S / W ), consequently causing mesophyll conductance ( g m ) and photosynthesis inhibition, especially under NH4 + supply. Conversely, males with a greater mesophyll palisade tissue thickness and chloroplast density, but a lower spongy cell density had lower S / W and higher S c / S, and higher g m and photosynthesis. NH4 + -fed females had a lower CO2 conductance through cell wall and stromal conductance perpendicular to the cell wall, but a higher chloroplast conductance from the cell wall ( g cyt1 ) than females supplied with NO3 −, whereas males had a higher chloroplast conductance and lower CO2 conductance through cell wall when supplied with NO3 − instead of NH4 + under salt stress. These findings indicate sex-specific strategies in coping with salt stress related to leaf anatomy and g m under both types of nitrogen supplies, which may contribute to sex-specific CO2 capture and niche segregation.